Double Choker: Double Aortic Arch with Bilateral Aortic Coarctation Associated with Heterotaxy-Asplenia Syndrome and Complex Atrioventricular Canal Defect - Dixon, Chandler M. (CASE (Phila), 2020)
[Figure: see text]